Laboratory-Confirmed Avian Influenza A(H9N2) Virus Infection, India, 2019 - Varsha Potdar; Dilip Hinge; Ashish Satav; Eric F. Simões; Pragya D. Yadav; Mandeep S. Chadha (Emerging Infectious Diseases, 2019)
A 17-month-old boy in India with severe acute respiratory infection was laboratory confirmed to have avian influenza A(H9N2) virus infection. Complete genome analysis of the strain indicated a mixed lineage of G1 and H7N3. The strain also was found to be susceptible to adamantanes and neuraminidase inhibitors.